Vibrational effects on the dynamic pressure measurement standard based on a diaphragmless shock tube. (December 2021) - Hristov, Ivan; Svete, Andrej; Kutin, Jože
Abstract: This paper determines the vibrational effects on a diaphragmless shock tube, which was developed for dynamic calibrations of pressure transducers. First, the sensitivity to acceleration of the piezoelectric pressure transducer was determined by exciting the end-wall shock tube flange with the pressure transducer mounted. Considering the obtained acceleration sensitivity of the pressure transducer and measured accelerations during the operation of the shock tube, the vibrational effects on the operating shock tube were estimated.